Multi-species response to rapid environmental change in a large estuary system: A biochronological approach. (October 2016) - Izzo, Christopher; Doubleday, Zoë A.; Grammer, Gretchen L.; Barnes, Thomas C.; Delean, Steven; Ferguson, Greg J.; Ye, Qifeng; Gillanders, Bronwyn M.
Highlights: Generalisations about ecosystem resilience may mask species-level responses. Fish growth chronologies quantify biological responses to environmental change. Sensitivity to environmental change is dependent on species ecological needs. Abstract: The sensitivity of species to environmental change is dependent on their ecological requirements (i.e. specialist v. generalist), and hence likely to be species-specific. Identifying species level variation in environmental sensitivity informs assessments of community vulnerability and assists in developing adaptive management strategies. We investigated species-specific sensitivity in fish to understand the vulnerability of differing life histories and ecological requirements to rapid environmental alteration (i.e. drought). Biochronologies of fish growth, based on increment widths in otoliths, were analysed using a mixed modelling approach. We assessed multi-decadal responses in fish growth to environmental variation in the terminal system of Australia's largest river, for three long-lived fish species with differing life histories and ecological requirements: a freshwater specialist and two estuarine generalists. Biochronologies were between 20 and 38 years long, spanned a decade of severe drought and showed considerable inter-annual variation in growth. Precipitation influenced the growth of the obligate freshwater specialist, Macquaria ambigua ambigua. Temperature and salinity influenced the growth of the two estuarine generalists: Argyrosomus japonicus (estuarine opportunist) and Acanthopagrus butcheri (estuarine dependent), respectively. These results suggest that generalisations about how species respond to environmental change may mask species-specific responses to dependent on the constraints of their ecological requirements (i.e. specialist v. generalist). These findings also highlight the importance of considering the diversity of life history strategies that inhabit an ecosystem when developing conservation and management strategies.